Determination of Salivary CD44 as a Noninvasive Diagnostic Biomarker to Predict Malignant Transformation of Oral Submucous Fibrosis - Rajalakshmi Rakshanaa; Nalini Aswath; Vijayalakshmi Ramshankar; Soundarya Ravindran; K. Mehanathan (Contemporary Clinical Dentistry)
Background: In the case of oral potentially malignant disorders such as oral submucous fibrosis (OSMF), leukoplakia and in oral cancer, cancer stem cells are reported to be present. Cluster of differentiation 44 (CD44) is a stem cell involved in various cellular regulation pathways and detected in proficient amounts as molecular biomarkers in saliva that are cleaved and released but surprisingly no evidence to support its diagnostic value in OSMF. Aim: The aim of the study was to determine the CD44 expression in the salivary sample of OSMF patients and to evaluate its effectiveness as a noninvasive diagnostic marker. Materials and Methods: Group 1 included 30 controls and Group 2 included 30 OSMF cases. Salivary samples were collected and subjected to enzyme-linked immunosorbent assay for determining the CD44 values. Grading of OSMF was done based on clinical examination and histopathological investigation. The data obtained were subjected to statistical analysis (SPSS Version 24) Chi-square test, independent t-test, one-way ANOVA, Pearson, and Spearman correlation were performed. Results: In Group 2, there was male predominance with 86.7% (n = 26) males. The mean CD44 expression in Group 1 (Normal) was 5.57 ± 0.77 pg/ml and the mean expression in Group 2 (OSMF) was 5.37 ± 0.76 pg/ml. There was a decrease of CD44 value in Group 2 (OSMF) when compared to Group 1 though not statistically significant. Similarly, the mean CD44 values decreased with the progression of grades of OSMF from 5.493 ± 0.278 in Grade 1 patients to 4.794 ± 1.020 in Grade 4B. Conclusion: Our study was the first of its kind to assess the expression of CD44 in OSMF patients. Results infer that CD44 may decrease with the progression of normal mucosa to OSMF and with different grades, however, future studies are required with larger sample size to determine CD44 as molecular biomarker.